Strategi Pemanfaatan Zakat, Infak, Sedekah (ZIS) di LAZ PERSIS (Persatuan Islam) Kota Bandung - febby bilqis; Nurfahmiyati (UNISBA Press, 2024)
Abstract. LAZ PERSIS (Islamic Union) is a national zakat, infak, and alms fund management institution that serves to improve the welfare of the people in the fields of education, da'wah, social, economic, and health. The problems faced by LAZ PERSIS are that the assistance and supervision in the independent community program is not optimal. The purpose of this study is to determine the strategy of using ZIS for the economy of people in LAZ PERSIS (Islamic Union) Bandung City. The research method used in this study is the qualifier-tatif method. The data used were the results of observations of interviews with internal parties LAZ PERSIS and mustahik Z Chicken. The results of the interviews that have been conducted are analyzed using SWOT analysis to determine the external and internal conditions of LAZ PERSIS. Based on the results of the study, it can be seen that the results of the SWOT analysis in the use of ZIS in LAZ PERSIS utilize strategies based on their strengths and opportunities (SO) resulting in aggressive strategies carried out by increasing public trust in the services of the Umat Mandiri pro-program. The strategy based on its strengths and threats (ST) resulted in a diversification strategy carried out by improving the taste quality of Z Chicken and evaluating the Umat Mandiri program, namely the Z Chicken business. This strategy is based on its weaknesses and opportunities (WO) resulting in a turn around strategy carried out by coaching muzakki and mustahik who follow the empowerment program. A strategy based on its weaknesses and threats (WT) results in a defensive strategy carried out with attention to quality and quality. Abstrak. LAZ PERSIS (Persatuan Islam) merupakan lembaga pengelola dana zakat, infak, dan sedekah nasional yang berkhidmat untuk meningkatkan kesejahteraan umat dalam bidang pendidikan, dakwah, sosial, ekonomi, dan kesehatan. Permasalahan yang dihadapi oleh LAZ PERSIS kurangnya pendampingan dan pengawasan dalam program umat mandiri kurang maksimal. Tujuan penelitian ini yaitu untuk mengetahui stategi pemanfaatan ZIS terhadap perekonomian umat di LAZ PERSIS (Persatuan Islam) Kota Bandung. Metode penelitian yang digunakan pada penelitian ini adalah metode kualitatif. Data yang digunakan adalah hasil observasi wawancara bersama dengan pihak internal LAZ PERSIS dan mustahik Z Chicken. Hasil wawancara yang telah dilakukan dianalisis menggunakan analisis SWOT untuk mengetahui kondisi eksternal dan internal LAZ PERSIS. Berdasarkan hasil penelitian, dapat diketahui bahwa hasil analisis SWOT dalam pemanfaatan ZIS di LAZ PERSIS memanfaatkan strategi yang didasarkan pada kekuatan dan peluang yang dimilikinya (SO) menghasilkan strategi agresif dilakukan dengan meningkatkan kepercayaan masyarakat terhadap pelayanan program. Umat Mandiri, Strategi yang didasarkan pada kekuatan dan ancaman yang dimilikinya (ST) menghasilkan strategi diversifikasi dilakukan dengan meningkatkan kualitas rasa dari Z Chicken dan mengevaluasi program Umat Mandiri yaitu usaha Z Chicken. Strategi ini didasarkan pada kelemahan dan peluang yang dimilikinya (WO) menghasilkan strategi turn around dilakukan dengan melakukan pembinaan terhadap muzakki dan mustahik yang mengikuti program pemberdayaan. Strategi yang didasarkan pada kelemahan dan ancaman yang dimilikinya (WT) menghasilkan strategi defensif dilakukan dengan memperhatikan kualitas dan mutu pelayanan dari program Umat Mandiri usaha Z Chicken dan monitoring secara berkala program Umat Mandiri yaitu Z Chicken.